Anthropic Exposure Indicator for River Basins Based on Landscape Characterization and Fuzzy Inference - Elfany Reis do Nascimento Lopes; Carlos de Souza, José; Paixão de Sousa, Jocy Ana [UNESP]; Filho, José Luiz Albuquerque; Lourenço, Roberto Wagner [UNESP] (Pleiades Publishing, 2021)
Abstract: The objective of this study is to develop an anthropic exposure indicator for river basins using quantitative and qualitative aspects of the landscape and morphometric analysis based on fuzzy logic and geoprocessing. The indicator was developed from a Mamdani type fuzzy inference system by integrating information regarding the calculation of the anthropic transformation index and the circularity index of the river basin and its watersheds. The anthropic transformation was obtained from the mapping of land and forest use plotted by visual interpretation of the orthorectified multispectral satellite image of RapidEye. The circularity index was calculated using the area of the territorial limits of the study area. The basin presented thirteen classes of uses, with a greater predominance of the anthropic agricultural area, occupied by temporary crops in approximately 3472 ha (36.33%). The vegetation cover has a greater predominance of forest fragments of dense Ombrophylous forest that measure approximately 3589 ha (37.05%). The indicator showed a medium to high anthropogenic exposure for the basin. Watershed 8 showed a high to very high exposure. The exposure indicator is a tool that details the anthropic exposure of watersheds based on the reality of the activities that occur within it and the morphometric capacity. It can be used for similar areas.
Keywords: geoprocessing; land use; memberships functions; water resources